Ruvbl2 Suppresses Cardiomyocyte Proliferation During Zebrafish Heart Development and Regeneration - Sharpe, Michka; González-Rosa, Juan Manuel; Wranitz, Felicia; Jeffrey, Spencer; Copenhaver, Katherine; Burns, C. Geoffrey; Burns, Caroline E. (Frontiers in Cell and Developmental Biology, 2022)
Cardiomyocyte proliferation is an important source of new myocardium during heart development and regeneration. Consequently, mutations in drivers of cardiomyocyte proliferation cause congenital heart disease, and infarcted human hearts scar because cardiomyocytes exit the cell cycle postnatally. To boost cardiomyocyte proliferation in either setting, critical regulators must be identified. Through an ENU screen in zebrafish, the liebeskummer (lik) mutant was isolated and described as having elevated cardiomyocyte numbers during embryogenesis. The lik mutation results in a three amino acid insertion into Ruvbl2, a highly conserved ATPase. Because both gain- and loss-of-function properties have been described for ruvbl2lik, it remains unclear whether Ruvbl2 positively or negatively regulates cardiomyocyte proliferation. Here, we demonstrate that Ruvbl2 is a suppressor of cardiomyocyte proliferation during zebrafish heart development and regeneration. First, we confirmed speculation that augmented cardiomyocyte numbers in ruvbl2lik/lik hearts arise by hyperproliferation. To characterize bona fide ruvbl2 null animals, we created a ruvbl2 locus deletion allele (ruvbl2Δ). Like ruvbl2lik/lik mutants, ruvbl2Δ/Δ and compound heterozygote ruvbl2lik/Δ animals display ventricular hyperplasia, demonstrating that lik is a loss of function allele and that ruvbl2 represses cardiomyocyte proliferation. This activity is autonomous because constitutive myocardial overexpression of Ruvbl2 is sufficient to suppress cardiomyocyte proliferation in control hearts and rescue the hyperproliferation observed in ruvbl2Δ/Δ mutant hearts. Lastly, heat-shock inducible overexpression of Ruvbl2 suppresses cardiomyocyte proliferation during heart regeneration and leads to scarring. Together, our data demonstrate that Ruvbl2 functions autonomously as a suppressor of cardiomyocyte proliferation during both zebrafish heart development and adult heart regeneration.